2013
DOI: 10.1055/s-0033-1333886
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Nasal Deformity and Rhinoplasty

Abstract: The cleft nasal deformity is a complex challenge in plastic surgery involving the skin, cartilage, mucosa, and skeletal platform. Ever since Blair and Brown first described the intricacies of the cleft pathology in 1931, the appropriate approach has been extensively debated in the literature with respect to timing, technique, and extent of surgical intervention. In this article, the authors review the literature and summarize the various modalities for achieving a successful rhinoplasty in the patient with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Successful surgical correction is often surgeon dependent and often based on their training and experience. In addition, the absence of a standardized link between the subject's age, physical development, and amount of revisions needed has led to disagreement in cleft rhinoplasty timing and techniques (Buchanan et al, 2012). Multiple studies have reported conflicting views regarding the utilization of cartilage grafting from various donor sites (Ozaki et al, 2006;Wee et al, 2015;Lu et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Successful surgical correction is often surgeon dependent and often based on their training and experience. In addition, the absence of a standardized link between the subject's age, physical development, and amount of revisions needed has led to disagreement in cleft rhinoplasty timing and techniques (Buchanan et al, 2012). Multiple studies have reported conflicting views regarding the utilization of cartilage grafting from various donor sites (Ozaki et al, 2006;Wee et al, 2015;Lu et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, many studies have reported normal nose growth after primary rhinoplasty. [ 24 25 ] Yoshimura et al . [ 23 ] performed an observational study with a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The profundus, while present, is hypoplastic and, rather than projecting anteriorly giving rise to a cutaneous-vermilion junction or white roll, terminates within the vermillion mucosa. 14 , 28 , 29 , 31 , 35 In addition, the course of the cleft segment’s paranasal muscle fibers from the ala to the anterior nasal spine is interrupted, contributing to nasal deviation. 36 , 37 These aberrant muscular insertions create facial imbalance further intensified by the degree of the retropositioned and hypoplastic maxillary cleft segment.…”
Section: Anatomy Of the Cleft Lip Nasal Deformitymentioning
confidence: 99%
“…Unopposed muscular forces result in an asymmetric nasal tip via displacement of the caudal septum, the cleft medial crural footplate, and columella toward the noncleft side and compensatory bowing of the septum, flaring of the cleft side LLC, and widening of the alar base towards the cleft side. 28 , 29 , 31 The LLC’s change in position affects its attachment to the upper lateral cartilage (ULC) and weakens both the upper lateral cartilage and scroll region.…”
Section: Anatomy Of the Cleft Lip Nasal Deformitymentioning
confidence: 99%